Sociological reflections on the neurosciences - Pickersgill, Martyn; Keulen, Ira Van (Advances in medical sociology, 2011)
The neurosciences are the new cutting edge in biomedicine, and this is the first book to take a sociological imagination to this field. The neurosciences are more than a collection of scientific practices they offer up new ways of thinking about mind, body and society. Up to now, debate about the new brain sciences has been limited within sociology. As the neurosciences gain ever more traction within professional arenas, policy processes and popular culture, it is time to go beyond the primarily speculative and theoretical analyses we have had to date, and bring our sociological imagination to bear. This collection addresses this need for sociological insight through empirically rich, theoretically innovative chapters that range across methods, traditions and foci in order to cast new light on the place, role and impact of neuroscience. At the same time, this volume reflects on the insights the neurosciences have to offer sociology. With cutting-edge contributions from leading scholars from Canada, Finland, France, Germany, Israel, the UK and the USA, Sociological Reflections on the Neurosciences will be a benchmark text in the new sociology of neuroscience.